WATER-SOLUBLE TRIS(HYDROXYMETHYL)PHOSPHINE COMPLEXES WITH NICKEL, PALLADIUM, AND PLATINUM - CRYSTAL-STRUCTURE OF [PD(P(CH2OH)3)4].CH3OH - Ellis, J; Harrison, K; Hoye, P; Orpen, A; Pringle, P; Smith, M (1992)
The large-scale synthesis of the water-soluble phosphine P(CH2OH)3 (1) from either PH3 or [P(CH2OH)4]Cl is described. Treatment of [MX2(COD)] (M = Pt or Pd; X = Cl, Br, or I; COD = cycloocta-1,5-diene) with 1 gives the corresponding [MX2{P(CH2OH)3}2] (2-7) complexes which are soluble in water, methanol, or dmso but insoluble in most common organic solvents. Methanolic or dmso solutions of the organoplatinum complex [Pt(CH3)2{P(CH2OH)3}2] (8) can be generated from 1 and [Pt(CH3)2(COD)], but 8 decomposes in concentrated solutions. Treatment of [PtCl(CH3)(COD)] with 1 gives the stable, water-soluble mixture of organoplatinum complexes cis- and trans-[PtCl(CH3){P(CH2OH)3}2] (9a,b) which reacts with LiBr or LiI to give the corresponding [PtX(CH3){P(CH2OH)3}2] (10 and 11). The zerovalent complex [Ni{P(CH2OH)3}4] (12) is made by adding 1 in methanol to a toluene solution of [Ni(COD)2] whereas the best method for synthesizing the palladium analogue 13 is by addition of an aqueous solution of 1 to a CH2Cl2 solution of [Pd(PPh3)4] followed by isolation of the product from the aqueous layer. The crystal structure of [Pd{P(CH2OH)3}4]·CH3OH shows the Pd(0) center to be tetrahedrally coordinated by P(CH2OH)3 ligands (Pd-P 2.326 (3), 2.321 (1) Å). The hydroxyl groups are all involved in either intramolecular or intermolecular OH⋯O hydrogen bonding (O⋯O distances 2.68 (1)-2.76 (1) Å). Treatment of a suspension of [Pt(PPh3)4] or [Pt(COD)2] in methanol with 1 gave a compound with composition [Pt{P(CH2OH)3}4]·H2O (14) which, from NMR and IR spectroscopy in solution, is shown to be an equilibrium mixture of [Pt{P(CH2OH)3}4] (14a) and the five-coordinate hydridoplatinum(II) complex [PtH{P(CH2OH)3}4]OH (14b). The chemical and spectroscopic properties of the complexes of 1 are compared with analogous PMe3 and PEt3 species, and it is concluded that, in many respects, 1 has coordination properties that would be expected of a small hydrophilic trialkylphosphine but, in addition, has some unique properties associated with the hydrogen bonding present among the coordinated P(CH2OH)3 ligands. © 1992 American Chemical Society.